Educational Participation of Families in a Valencian Public School. A Qualitative Study - Andrés Payà Rico; Marta Tormo Tormo (FahrenHouse, 2016)
In the present article we carry out a field study in a state school located in Carcaixent (from Valencia) about the different perceptions, reflections and impressions of the faculty, management team, Parents Association (AMPA) and parents from the political and critical reflection about the active participation of families. Thanks to a set of semi-structured interviews, its transcription and further analysis of its contents, we have obtained valuable conclusions and reflections which indicate the importance that families give to participation, to the point that they are immerse in the process of transformation in a learning community (CdA). Among the conclusions obtained in the mentioned qualitative study, we have been able to observe the familiar perceptions about participation, the existing obstacles and determinants for it, the relationship between the different members of the educational community, the channels of participation, etc.; a whole range of considerations which provide useful information of political and pedagogical character. These considerations can orientate the implementation of school participation policies and the construction of a cohesive and active educational community.